2021
DOI: 10.1186/s41235-021-00270-9
|View full text |Cite
|
Sign up to set email alerts
|

A starring role for inference in the neurocognition of visual narratives

Abstract: Research in verbal and visual narratives has often emphasized backward-looking inferences, where absent information is subsequently inferred. However, comics use conventions like star-shaped “action stars” where a reader knows events are undepicted at that moment, rather than omitted entirely. We contrasted the event-related brain potentials (ERPs) to visual narratives depicting an explicit event, an action star, or a “noise” panel of scrambled lines. Both action stars and noise panels evoked large N400s compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The consistently longer viewing times at the subsequent panel suggested that these viewing time differences did not pertain to deepness of processing, but rather to differences in surface-level structures. The faster viewing times made to action stars and onomatopoeias specifically seemed related to visual complexity of the panels themselves (Cohn, 2021; Cohn & Wittenberg, 2015). The results supported SPECT’s (Loschky et al, 2020) predictions that less content should require fewer eye fixations, and thus result in faster viewing times.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The consistently longer viewing times at the subsequent panel suggested that these viewing time differences did not pertain to deepness of processing, but rather to differences in surface-level structures. The faster viewing times made to action stars and onomatopoeias specifically seemed related to visual complexity of the panels themselves (Cohn, 2021; Cohn & Wittenberg, 2015). The results supported SPECT’s (Loschky et al, 2020) predictions that less content should require fewer eye fixations, and thus result in faster viewing times.…”
Section: Discussionmentioning
confidence: 99%
“…Among the inexplicit techniques, metaphors were also rated low, possibly due to the extended updating needed to interpret them, whereas action stars were rated high. Their ratings may have been motivated by their familiarity, as conventionalized units within comics (Cohn, 2021; Cohn & Wittenberg, 2015), arguably more so than metaphors. Moreover, action star sequences were viewed faster than metaphor sequences, and potentially comprehensibility ratings reflect the effort required for inference resolution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations